Life expectancy in individuals with type 1, type 2 diabetes and without diabetes: a systematic review and meta-analysis - Ezzatvar, Yasmin; López-Gil, José Francisco; Yáñez-Sepúlveda, Rodrigo; Hurtado-Almonacid, Juan; García-Hermoso, Antonio (Frontiers in Endocrinology, 2025)
The aim of the study was to estimate and compare life expectancy among individuals with type 1 diabetes (T1D), type 2 diabetes (T2D) and without diabetes according to sex, geographical regions and study periods. Years of potential life lost (YPLL) was assessed as a secondary outcome. We conducted a systematic review and meta-analysis following PRISMA guidelines. PubMed, EMBASE, and Web of Science were searched from inception to June 2025 for studies reporting life expectancy in individuals with T1D, T2D, and those without diabetes. Two reviewers independently screened and extracted data. Life expectancy estimates were pooled using random-effects models with empirical Bayes estimation, and heterogeneity was quantified using the I² statistic and between-study variance (τ²). We calculated 95% confidence (CI) and prediction intervals (PI) and conducted subgroup analyses by sex and geographical region. Meta-regression assessed cohort year effects, using the median year when a range was reported, and publication bias was evaluated using Doi plots and the Luis Furuya-Kanamori (LFK) index. Twenty-three studies including 179 cohorts were identified, encompassing 65,271 individuals with T1D and over 139 million with T2D. Life expectancy was shortest among individuals with T1D: 65.12 years (95%CI: 59.51–70.72; PI: 41.22–88.98) in men and 68.26 years (95%CI: 63.01–73.51; PI: 47.26–89.23) in women. For T2D, life expectancy was 74.34 years (95%CI: 72.81–75.87; PI: 61.32–87.28) in men and 79.63 years (95%CI: 78.32–80.95; PI: 68.36–90.83) in women. By comparison, men and women without diabetes lived on average 79.56 years (95%CI: 77.98–81.15; PI: 75.81–83.46) and 84.46 years (95%CI: 83.38–85.54; PI: 81.54–87.47), respectively (all p<0.001). YPLL was 11.3 for men and 10.9 for women with T1D, and 7.0 and 6.2 for men and women with T2D, respectively. In conclusion, life expectancy remains substantially lower than in the non-diabetic population, particularly for T1D, although temporal improvements were observed. Our results highlight persistent disparities in longevity between diabetes types, sexes, and regions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251074407.